A Method for Soil Samples Collection during Site Assessment for Aquaculture : Sampling method to assess soil for aquaculture - Shafi, Javairia; Waheed, Kashifa N.; Mirza, Zahid S.; Zafarullah, Muhammad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Assessment of soil quality is one of the crucial steps during the assessment of a site for aquaculture. However, no clear guidelines are available in literature to guide fish farmers about soil sample collection resulting in a waste of their time and energy. The present study was, therefore, designed to determine the variability of soil characteristics at different sites and give recommendations for sample collection during soil assessment. Two hundred and eighty-six (286) soil samples collected from different subsites of seven sampling sites were analyzed for particle size distribution and chemical parameters. Results showed significant variation in soil separate content at different subsites of a sampling site. At Moza Bahak Maken in district Sargodha, the soil was found to be sandy at one subsite and clayey on the other within 35 acres of land area. Moreover, significant differences in soil quality parameters were also found with varying sampling depths. pH of soil indicated the calcareous nature of the soil in Punjab and outruled the necessity to lime soil. Electrical conductivity measurements showed that soil in the Sargodha division can be characterized as very strongly saline. The study led to the conclusion that sample collection for soil analysis in aquaculture should be based on stratified sampling selecting at least three sampling points from each stratum. Soil samples should be collected in 1 ft. increment from the surface up to the depth that should be 1 ft. deep than the soil depth that will be dug in excavated ponds. Culturable fish/ shrimp species should be selected based on the salinity of soil at the proposed fish pond site.